Curtailment as a successful method for reducing bat mortality at a southern Australian wind farm. (10th July 2022) - Bennett, Emma M.; Florent, Stevie Nicole; Venosta, Mark; Gibson, Matthew; Jackson, Alex; Stark, Elizabeth
Abstract: Wind energy is a rapidly expanding renewable technology with massive global investments; however, operating turbines are associated with bat strikes globally, and evidence suggests that without intervention, wind farm collisions could drive some common species to extinction. One widely regarded method for reducing strike mortality is operational mitigation, or curtailment, where turbine operation is restricted at low wind speeds. Despite an increasing number of studies in the Northern Hemisphere demonstrating curtailment effectiveness, no empirical studies have yet been conducted in Australia. This paper reports the findings of a curtailment study implemented at the Cape Nelson North wind farm in southwest Victoria, Australia. Conservation detection dog teams conducted mortality surveys between January and April in 2018 (before; pre‐curtailment) and 2019 (after; during curtailment). Results were consistent with similar studies in the USA and Europe, as curtailment significantly reduced pooled species mortality by 54%. Bat calls did not decline during the study period, and thus were not an explanation for the reduction in fatalities. This study demonstrates that curtailment is a valid method for reducing bat turbine collision in south‐eastern Australia. Consideration should be given to curtailment as a means to reduce bat turbine impacts in Australia, particularly at sites with known endangered and threatened populations, as we act to reduce anthropogenic climate change and its time‐sensitive negative consequences.